Influence of core extension and side chain nature in targeting G-quadruplex structures with perylene monoimide derivatives - Busto, Natalia; García-Calvo, José; Cuevas, José Vicente; Herrera, Antonio; Mergny, Jean-Louis; Pons, Sebastian; Torroba, Tomás; García, Begoña (Bioorganic chemistry, 2021)
A structure-activity relationship (SAR) study in terms of G-quadruplex binding ability and antiproliferative activity of six fluorescent perylenemonoimide (PMIs) derivatives is reported. A positive charge seems to be the key to target G4. This study also reveals the importance of the element substitution in the potential biological activity of PMIs, being the polyethylene glycol (PEG) chains in the peri position responsible for their antiproliferative activity. Among them, the cationic PMI6 with two PEG chains is the most promising compound since its fluorescence is enhanced in the presence of G-quadruplex structures. Moreover, PMI6 binds to the human telomeric G-quadruplex hTelo with high affinity and displays a high antiproliferative potential towards HeLa (cervical adenocarcinoma), A549 (lung adenocarcinoma) and A2780 (ovarian adenocarcinoma) cells. Its fate can be followed inside cells thanks to its fluorescent properties: the compound is found to accumulate in the mitochondria.
Keywords: proliferace buněk; vztah mezi dávkou a účinkem léčiva; Antiproliferative; Mitochondria; Imides; Molecular Structure; Structure-Activity Relationship; Perylenemonoimide; lidé; Perylene; G-quadruplexes; perylen; kultivované buňky; imidy; mitochondrie; G-kvadruplexy; molekulární struktura; Cells, Cultured; Dose-Response Relationship, Drug; G-Quadruplexes; Cell Proliferation; vztahy mezi strukturou a aktivitou; DNA binding; Humans